A pyrolysis study of allylic hydrocarbon fuels. Issue 12 (17th August 2020) - Nagaraja, Shashank S.; Kukkadapu, Goutham; Panigrahy, Snehasish; Liang, Jinhu; Lu, Haitao; Pitz, William J.; Curran, Henry J.
Abstract: The pyrolysis of selected C3 –C5 allylic hydrocarbons has been studied using a single‐pulse shock tube. A new single‐pulse shock tube has been designed and constructed by recommissioning an existing conventional shock tube. This facility enables the investigation of high‐temperature chemical kinetics with an emphasis on combustion chemistry. The modifications performed on the existing shock tube are described, and the details of the sampling system to analyze the species concentration using a gas chromatography‐mass spectrometry‐flame ionization detection (GC‐MS with a flame ionization detector) system are also provided. This facility is characterized and validated by performing cyclohexene pyrolysis experiments. Furthermore, the performance of the shock tube is demonstrated by reproducing previous literature measurements on the pyrolysis of isobutene. Postvalidation, this setup is used to study the pyrolysis of trans ‐2‐butene and 2‐methyl‐2‐butene (2M2B). A newly developed mechanism, NUIGMech1.0, is used to simulate the experimental data of propene, isobutene, 2‐butene, and 2M2B, allylic hydrocarbon fuels. A description using two different kinetic simulation approaches is provided using our isobutene experiments as a reference. We found no significant differences between the two methods. Additionally, the contribution of different reaction classes on fuel consumption is detailed and the influence of geometry on fuel consumption and first aromatic ring: benzene is discussed.